Temporal discrimination deficits as a function of lag interference in older adults. Issue 10 (3rd June 2014) - Roberts, Jared M.; Ly, Maria; Murray, Elizabeth; Yassa, Michael A.
ABSTRACT A vital component of episodic memory is the ability to determine the temporal order of remembered events. Although it has been demonstrated that the hippocampus plays a crucial role in this ability, the details of its contributions are not yet fully understood. One proposed contribution of the hippocampus is the reduction of mnemonic interference through pattern separation. Prior studies have used behavioral paradigms designed to assess this function in the temporal domain by evaluating the ability to determine the order of remembered events as a function of proximity in time. Results from these paradigms in older adults (OA) have been mixed, possibly due to limitations in controlling elapsed time and narrow range of temporal lags. Here, we introduce a novel behavioral paradigm designed to overcome these limitations. We report that OAs are impaired relative to younger adults at moderate and high temporal lags but not at low lags (where performance approached floor). We evaluated OAs' ability to benefit from primacy (enhanced order judgment on the first few items of any given sequence) and found two distinct subgroups: one group was on par with young adults [aged‐unimpaired (AU)] and the other group was two standard deviations below the mean of young adults [aged‐impaired (AI)]. Temporal discrimination performance in AU adults was consistent with a pattern separation deficit, while performance in AI adults was consistent with a generalized temporal processing deficit. We propose that the task introduced is a sensitive marker for episodic memory deficits with age, and may have diagnostic value for early detection of age‐related pathology. © 2014 Wiley Periodicals, Inc.